Automated and virus variant-programmable surrogate test qualitatively compares to the gold standard SARS-CoV-2 neutralization assay - Danielle W. Ali; Maggie L. Bartlett; Christopher D. Heger; Francisco Ramirez; Linwood Johnson; Kevin L. Schully; Eric D. Laing; Wei Wang; Carol D. Weiss; Emilie Goguet; Christopher C. Broder; Stephanie A. Richard; et al. (npj Viruses)
Abstract The ongoing emergence of new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants underscores the need for rapid, adaptable, high-throughput testing. However, assays for neutralizing antibodies, which are a good measure of viral protection, usually require cell culture and either infectious SARS-CoV-2 or pseudotyped viral particles. To circumvent the challenges of cell-based assays, SARS-CoV-2 surrogate virus neutralization tests (sVNTs) measure inhibition of the binding of the spike (S) protein receptor binding domain (RBD) to its receptor, human angiotensin-converting enzyme 2 (hACE2) by neutralizing antibodies. Here we tested a prototype automated microfluidic cartridge-based sVNT platform using SARS-CoV-2 wild-type (WT) and B.1.617.2 (Delta) variant RBDs. This sVNT showed a high correlation with cell-based neutralization assays for biospecimens collected post-COVID-19 vaccination and post-SARS-CoV-2 infection as well as for pre-pandemic SARS-CoV-2 negative sera. Thus, this assay, which takes less than 80 min, is a relatively simple, safe, and accurate alternative to traditional VNTs.